Lauren Histologic Type Is the Most Important Factor Associated With Pattern of Recurrence Following Resection of Gastric Adenocarcinoma. Issue 1 (January 2018) - Lee, Jun H.; Chang, Kevin K.; Yoon, Changhwan; Tang, Laura H.; Strong, Vivian E.; Yoon, Sam S.
Abstract : Objective: To examine sites of initial recurrence in patients after resection of gastric and gastroesophageal junction Siewert II/III adenocarcinoma (GA). Background: There are few recent studies on recurrence for Western patients following potentially curative resection of GA. Methods: A review of a prospectively maintained, single institution database was performed. Clinicopathologic factors, site(s) of initial recurrence, disease-free survival, and overall survival were examined. Results: From January 2000 to June 2010, 957 patients underwent potentially curative resection for GA, 435 patients (46%) had recurrent disease, and complete data on recurrence site(s) could be obtained in 386 patients. Tumors were Lauren intestinal type in 206 (53%) and diffuse or mixed-type in 180 (47%). Median time to recurrence was 12 months and 75% of recurrences occurred within 2 years. There was a significant difference in pattern of initial recurrence between the intestinal and diffuse/mixed cohorts ( P < 0.001). For intestinal tumors, distant metastasis was the most common site (54%), followed by locoregional (20%), peritoneal (15%), and multifocal (11%). For diffuse/mixed tumors, peritoneal recurrence was the most common (37%), followed by distant (32%), locoregional (22%), and multifocal (9%). On multivariate analysis, Lauren histologic type was the only significant factor that was associated with both peritoneal recurrence (diffuse, hazard ratio 2.22, confidence interval 1.38–3.94) and distant recurrence (intestinal, hazard ratio 1.888, confidence interval 1.202–2.966). After recurrence, median overall survival was only 8.4 months. Conclusions: In GA patients who recur after resection, patterns of recurrence vary significantly based on Lauren histologic type.